2009
DOI: 10.1007/s10701-009-9390-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Possibility of Supertasks in General Relativity

Abstract: Malament-Hogarth spacetimes are the sort of models within general relativity that seem to allow for the possibility of supertasks. There are various ways in which these spacetimes might be considered physically problematic. Here, we examine these criticisms and investigate the prospect of escaping them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In his seminal analysis of computation, Turing [6] discussed the nature of human computation, and showed that certain tasksmost famously, the Halting Problem (HP) -are not decidable by computational means. Subsequent theoretical investigation by various researchers suggests, however, that physical systems may exist which can in fact decide HP by exploiting cosmological phenomena [7][8][9][10][11][12]. We focus here on one particular scheme for cosmological hypercomputation [9,13], and consider the extent to which it rests on secure logical foundations.…”
Section: Introductionmentioning
confidence: 99%
“…In his seminal analysis of computation, Turing [6] discussed the nature of human computation, and showed that certain tasksmost famously, the Halting Problem (HP) -are not decidable by computational means. Subsequent theoretical investigation by various researchers suggests, however, that physical systems may exist which can in fact decide HP by exploiting cosmological phenomena [7][8][9][10][11][12]. We focus here on one particular scheme for cosmological hypercomputation [9,13], and consider the extent to which it rests on secure logical foundations.…”
Section: Introductionmentioning
confidence: 99%
“…Another worry in the literature concerns communication between the computer and the programmer. The new-relative to [12, p.118], [26] or to [17]-feature we propose in section 4.1 is that we send the message not via light-signals but via a postman (not inertial and slower than the speed of light). It is a future task to check whether in the Kerr spacetime there is a sequence of worldlines for postmen starting from a cofinal set of events in the worldline of the computer such that there is a common bound for the acceleration in these worldlines.…”
Section: Resultsmentioning
confidence: 99%
“…In anti-de-Sitter spacetime each event is an MH event. The spacetime of an electrically charged black hole (called a Reissner-Nordström spacetime) is MH, spacetimes with closed timelike curves are MH, and there are many other examples [12, sec.4], [22,26]. Figure 4: Conformal (or Penrose) diagram of a slowly rotating black hole.…”
Section: Relativistic Computers In a General Settingmentioning
confidence: 99%
See 2 more Smart Citations